2015
DOI: 10.1097/scs.0000000000001201
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Coenzyme Q10 on the Regeneration of Crushed Facial Nerve

Abstract: Although many treatment methods have been tried to accelerate facial nerve regeneration after trauma, a definitive method has not been found yet. Co Q for the treatment of acute facial paralysis is promising on both physiologic assessments and pathologic evaluation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 24 publications
1
8
0
Order By: Relevance
“…Another antioxidant that has been studied for use in supporting the regeneration of crushed facial nerve is coenzyme Q. 24 Coenzyme Q was also found to be effective in promoting the regeneration of the nerve in an experimental facial nerve crush rat model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another antioxidant that has been studied for use in supporting the regeneration of crushed facial nerve is coenzyme Q. 24 Coenzyme Q was also found to be effective in promoting the regeneration of the nerve in an experimental facial nerve crush rat model.…”
Section: Discussionmentioning
confidence: 99%
“…There are a number of nerve integrity monitoring devices available to identify and preclude persistent nerve damage. 28 , 29 In this study, we used the Nerve Integrity Monitor facial electromyography technique described by Delgado et al 29 and used in several previous studies 15 , 24 to record the contraction of facial muscles. In the present study, although not reaching statistical significance, there was improvement in facial nerve function in the ozone group when assessed using threshold levels.…”
Section: Discussionmentioning
confidence: 99%
“…This is in accordance of Ozbay et al [18] who reported that there was improvement in facial nerve function after ozone therapy. This regeneration was evaluated by assessment of the degree of macrovacuolization, vascular congestion, and myelin sheath thickness [44] . Valko et al [45] suggested that Ozone may promote a moderate oxidative stress that in turn increases endogenous antioxidant systems leading to a decrease in free radicals.…”
Section: Discussionmentioning
confidence: 99%
“…The main cause in the therapy of ELP is complete withdrawal of patients’ painful symptoms, epithelialization of the eroded mucosal lesions and oral carcinoma prevention. There are various therapeutic procedures described and implemented in practice till this day including topical medications, steroid ointments, ultraviolet rays (PUVA) [ 15 ] and laser [ 16 ]. However, the era of new medications increasingly conquers the world, and is also applied in the treatment of the oral mucosal lesions, including ELP.…”
Section: Discussionmentioning
confidence: 99%